2015
DOI: 10.2174/1874306401509010009
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vaccination on Influenza-Related Respiratory Failure and Mortality in Hospitalized Elderly Patients Over the 2013-2014 Season

Abstract: Background : Seasonal Influenza (“the flu”) is a respiratory illness caused by influenza viruses. Yearly influenza vaccination is considered to be protective against illness and/or severity of illness and is recommended by CDC for all individuals > 6 months of age. However, the effectiveness of influenza vaccine in older individuals has come under question.Objectives : To describe the clinical characteristics and treatment outcomes of patients admitted to an academic tertiary care Veterans Administration hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In addition, 2 smaller studies assessed 2013–14 influenza vaccination in adults and its effects on disease severity. One of them [31] reported no effect of influenza vaccination on in-hospital mortality or respiratory failure among older adults hospitalized with influenza. In contrast, the other study reported lower influenza vaccination rates among those who presented with more severe respiratory illness, including need for ICU admission and positive pressure ventilation [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2 smaller studies assessed 2013–14 influenza vaccination in adults and its effects on disease severity. One of them [31] reported no effect of influenza vaccination on in-hospital mortality or respiratory failure among older adults hospitalized with influenza. In contrast, the other study reported lower influenza vaccination rates among those who presented with more severe respiratory illness, including need for ICU admission and positive pressure ventilation [32].…”
Section: Discussionmentioning
confidence: 99%
“…a virus or bacterium) is encountered.) [ [105] , [106] , [107] , [108] ]; Prior Influenza Infection/Vaccination (effects of prior influenza infection/vaccination on severity of future disease symptoms) [ [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] ]; Timing between Viral Exposures (elapsed time between viral exposures) [ [117] , [118] , [119] , [120] ]; Vaccine-Associated Enhanced Respiratory Disease (where vaccination enhances respiratory disease) [ [121] , [122] , [123] ]; Chronic Immune Activation (continuous innate immune responses) [ [124] , [125] , [126] ]. …”
Section: Resultsmentioning
confidence: 99%
“…Prior Influenza Infection/Vaccination (effects of prior influenza infection/vaccination on severity of future disease symptoms) [ [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] ];…”
Section: Resultsmentioning
confidence: 99%
“…Yet some subsets of population are at higher risk for more severe disease which may require hospitalization and/or intensive care unit admission due to complications such as pneumonia or acute respiratory distress. It is well known that the elderly (≥65 years of age) have the highest risk of increased morbidity including respiratory failure, and mortality; It is estimated that over 60% of all seasonal-influenza-related hospitalizations and 90% of seasonal-influenza-related deaths each year occur in the elderly [2,[3][4][5][6][7] in Europe [9], suggest that vaccination offered only slight protection for severe outcome due to this fact and because there was a high proportion of elderly hospitalizations (79.1%) and that older age is associated with a lower ICU admission [10].Data on the inverse relation between age and ICU admission has also been pointed out by other authors who found higher rate of ICU admission among SHCIC at 15-64 y [11][12][13][14].…”
Section: Discussionmentioning
confidence: 98%